STUDI SALURAN DRAINASE PADA JALAN MUSO SALIM BARONG TONGKOK KABUPATEN KUTAI BARAT - SASVANTELA, HERI (KURVA S JURNAL MAHASISWA, 2014)
Flooding is a state  of natural disaster phenomena which are related to the amount of damage in terms of life and material. Flooding began increasing population, climate change and land use change. Small drainage capacity and the amount of sediment in the drainage causing inundation / flooding. Other issues also arise from domestic waste water. Dense urban areas can’t processindividual waste water. So that, the waste water will flow inti the urban drainage system.In this study , rain fall plays an important role in the evaluation and planningof urban drainage. The data needed rain fall data, data on land use and topographic dat. Rain falldata were analyzed data used is the maximum daily rainfall data pahoman station with other stations comparisons. Rainfall data were analyzed with Log Person III and Gumbelthen tested with Chi Square for selecting distributions received. Rainfall datais then applied to the hourly rainfall intensity mononobe method.intensity of rain isuseful to calculate the peak discharge by rational methods. Based on data, flood from The several channels at Rarakuta  as polres road, Simpang Busur  road, Muso Salim road, Cut Nyak Dien road and Simpang Raya road.The evaluation was done by analysis of the discharge of each drainage channel acrossthe Muso Salim. After an evaluation there are several drainage channelsneed to redesign like Kartini channel and Teuku Umar channel, and some drainagechannels need to be normalized as Cut Nyak Dien channel, Imam Bonjol channel and  Barong Tongkok  channel.